2018
DOI: 10.3854/crm.5.107.tornieri.v1.2018
|View full text |Cite
|
Sign up to set email alerts
|

Malacochersus tornieri (Siebenrock 1903) – Pancake Tortoise, Tornier’s Tortoise, Soft-shelled Tortoise, Crevice Tortoise, Kobe Ya Mawe, Kobe Kama Chapati

Abstract: The Pancake Tortoise, Malacochersus tornieri (family Testudinidae), is a small, flat, and soft tortoise of up to about 17.8 cm carapace length, rarely weighing more than 500 g. It has a flat and pliable shell resulting from limited bony shell development with a covering of thin keratinous scutes. The flat shape and shell pliability are fundamental adaptations which have enabled the species to successfully utilize rock crevice microhabitats in East Africa. The species occurs widely but disjunctly in Kenya and T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…'No trend' in the other stations implied that since there were no translocations out of them, the tortoises initially present remained in the crevices throughout the study period. Considering that reproduction rate in the species is low (Spawls et al 2002;Schmidt 2006;Mwaya et al 2018), and our observations that the few hatchlings/juveniles which are reprod uced always find refuge farther away from the adult tortoise crevices, the tortoise numbers in the short term were unlikely to increase hence the constant number in the crevices over the study duration. Our results ultimately show that the tortoises always abided by their crevices and if displaced returned home alluding to strong site fidelity.…”
Section: Discussionmentioning
confidence: 67%
“…'No trend' in the other stations implied that since there were no translocations out of them, the tortoises initially present remained in the crevices throughout the study period. Considering that reproduction rate in the species is low (Spawls et al 2002;Schmidt 2006;Mwaya et al 2018), and our observations that the few hatchlings/juveniles which are reprod uced always find refuge farther away from the adult tortoise crevices, the tortoise numbers in the short term were unlikely to increase hence the constant number in the crevices over the study duration. Our results ultimately show that the tortoises always abided by their crevices and if displaced returned home alluding to strong site fidelity.…”
Section: Discussionmentioning
confidence: 67%
“…Research on Tanzanian population showed that males begin to mature at 90–100 mm and females at 130–140 mm carapace length (Moll and Klemens 1996). In captivity, pancake tortoises are known to reach sexual maturity at the age of 5–9 yrs and between 90 and 100 mm, depending on sex and growth rate; a life span of about 25 yrs has been reported (Mwaya et al 2018 and references therein). Some captive facilities have even reported a lifespan of about 40 yrs (Association of Zoos and Aquariums-AZA, Species Survival Plans–SSP programs, www.aza.org).…”
Section: Discussionmentioning
confidence: 99%
“…Adults are normally less than 20 cm in carapace length with a maximum weight of about 500 g (Moll and Klemens 1996; Malonza 2003). The species is found in scattered rocky hills, outcrops, and kopjes within the Precambrian basement rock system in arid and semiarid areas of south-eastern, central, and northern Kenya (Loveridge 1957; Malonza 2003; Spawls et al 2018), northern, eastern, and central Tanzania (Loveridge 1957; Moll and Klemens 1996; Spawls et al 2018), and northern Zambia (Chansa and Wagner 2006; Mwaya et al 2018; Eustace et al 2021). The major threat to this wild species has been over-collection for the international pet trade (Klemens and Moll 1995; Malonza 2003).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, observations of pancake tortoises outside of rock crevices are rare because the species prefers to hide inside rock crevices (Klemens & Moll, 1995). Out‐of‐crevice forays appear to be brief, with tortoises moving directly between crevices along easily navigable routes (Moll & Klemens, 1996; Mwaya, 2002; Mwaya et al, 2018). For example, males have been observed visiting females in different crevices (Moll & Klemens, 1996; Mwaya, 2006) seasonally (Malonza, 2003) suggesting that pancake tortoises do move between crevices.…”
Section: Introductionmentioning
confidence: 99%